From Prevention To Response: A Comprehensive Scientific Review Of Health Security (The Review of Diabetic Studies, 2025)
Health security is a multifaceted concept encompassing activities and measures aimed at minimizing the danger and impact of acute public health events that threaten population health across geographical and sovereign boundaries. Its historical evolution spans from early international epidemic control efforts to the modern paradigm of global health security, underpinned by principles of universal health coverage, intersectoral coordination, and ethical and legal foundations. Health security is critically influenced by biological determinants such as emerging infectious diseases and antimicrobial resistance, environmental factors including climate change and biodiversity loss, and sociopolitical determinants like governance structures and international cooperation. Technological innovations and economic factors also shape health security by enhancing diagnostic capabilities, vaccine development, and resource distribution. Effective prevention strategies involve primary measures such as zoonotic surveillance and immunization programs, secondary interventions including screening and risk communication, and the integrated One Health approach. Preparedness hinges on developing core capacities under the International Health Regulations, risk assessment and modeling, health system strengthening, and public health laboratories with genomic surveillance capabilities. Outbreak response and emergency management involve epidemiological interventions, clinical and public health measures, the critical roles of frontline workers, effective communication and trust management, and multisectoral coordination. Recovery and resilience building focus on post-event evaluation, health system restoration, psychological and social healing, economic regeneration, and strategic investments to mitigate future risks. Technological advancements in digital health systems, artificial intelligence, vaccinology, genomic medicine, and remote sensing are transforming health security, while data security and ethical considerations remain paramount. This comprehensive review explores the conceptual foundations, determinants, prevention, preparedness, response, recovery, and innovation dimensions of health security, aiming to inform effective approaches to protect populations worldwide.